2022
DOI: 10.1002/solr.202200346
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Hydrothermal Synthesis of Metallic Bi Self‐Deposited Bi2SiO5 with Enhanced Photocatalytic CO2 Reduction Performance

Abstract: Metal‐modified nanomaterial has been regarded as an effective way to improve its photocatalytic CO2 reduction performance. Herein, metallic Bi self‐doped Bi2SiO5 composites are successfully in situ synthesized via a simple OH−‐assisted hydrothermal controllable route. The experimental results reveal that 2 mol L−1 NaOH plays two roles in the formation of Bi/Bi2SiO5 composites: 1) increasing the specific surface area through cracking the flower‐like microspheres of Bi2SiO5 with the increase of pH value, 57.92 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…The lattice spacing of the dots was measured around 0.327 nm (Figure 1F), which matched well with the (012) plane of metallic Bi (JCPDS No. 441246), 38,39 confirming the formation of metallic Bi nanoparticles. The energy‐dispersive X‐ray mapping confirmed that the Bi, Cl, and O elements were uniformly distributed throughout the nanosheet (Figure ).…”
Section: Resultsmentioning
confidence: 78%
“…The lattice spacing of the dots was measured around 0.327 nm (Figure 1F), which matched well with the (012) plane of metallic Bi (JCPDS No. 441246), 38,39 confirming the formation of metallic Bi nanoparticles. The energy‐dispersive X‐ray mapping confirmed that the Bi, Cl, and O elements were uniformly distributed throughout the nanosheet (Figure ).…”
Section: Resultsmentioning
confidence: 78%
“…All characterizations mentioned earlier prove that the ZnSO-0.75Pt could increase the generation, separation, and transport of photogenerated electron/hole pairs, leading to high photocatalytic performance of CO 2 reduction. [51,52] Furthermore, the N 2 adsorption-desorption isotherms were conducted and the specific surface area of ZnO, ZnS, ZnSO-0.50, and ZnSO-0.75Pt was 3.25, 21.72, 9.95, and 12.38 m 2 g À1 , respectively (Figure S11, Supporting Information). Although the ZnS showed the highest specific surface area, which should have more active sites, the performance was the worst, strongly suggesting that high-efficiency separation and transfer of charge carriers were of vital importance to photocatalytic CO 2 reduction.…”
Section: Resultsmentioning
confidence: 99%
“…All characterizations mentioned earlier prove that the ZnSO‐0.75Pt could increase the generation, separation, and transport of photogenerated electron/hole pairs, leading to high photocatalytic performance of CO 2 reduction. [ 51,52 ]…”
Section: Resultsmentioning
confidence: 99%